Differentiation of Melipona quadrifasciata L. (Hymenoptera, Apidae, Meliponini) subspecies using cytochrome b PCR-RFLP patterns - Rogério O. Souza; Geraldo Moretto; Maria C. Arias; Marco A. Del Lama (Genetics and Molecular Biology, 2008)
Melipona quadrifasciata quadrifasciata and M. quadrifasciata anthidioides are subspecies of M. quadrifasciata, a stingless bee species common in coastal Brazil. These subspecies are discriminated by the yellow stripe pattern of the abdominal tergites. We found Vsp I restriction patterns in the cytochrome b region closely associated to each subspecies in 155 M. quadrifasciata colonies of different geographical origin. This mitochondrial DNA molecular marker facilitates diagnosis of M. quadrifasciata subspecies matrilines and can be used to establish their natural distribution and identify hybrid colonies.